2008
DOI: 10.1158/1541-7786.mcr-07-0162
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Rab27A Gene by Breast Cancer Cells Promoting Invasiveness and the Metastasis Potential by Secretion of Insulin-Like Growth Factor-II

Abstract: In addition to the functions of transporting melanosome in melanocytes and releasing contents of lytic granules in CTLs, Rab27A was recently shown to be involved in exocytosis of insulin and chromaffin granules in endocrine cells; it was also reported to be expressed in an exceptionally broad range of specialized secretory cells. As autocrine and paracrine cytokines are essential for invasion and metastasis in some solid tumors, blocking them may be an effective strategy to prevent tumor dissemination. In the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 67 publications
2
70
0
Order By: Relevance
“…Cell cycle and apoptotic analyses were performed by flow cytometry (FCM) as previously described using an FACScalibur system (Wang et al, 2008). Apoptotic cells were analyzed by quadrant statistics of the propidium iodidenegative and annexin V-positive cells.…”
Section: Cell Proliferationmentioning
confidence: 99%
“…Cell cycle and apoptotic analyses were performed by flow cytometry (FCM) as previously described using an FACScalibur system (Wang et al, 2008). Apoptotic cells were analyzed by quadrant statistics of the propidium iodidenegative and annexin V-positive cells.…”
Section: Cell Proliferationmentioning
confidence: 99%
“…Rab27B exhibits a peripheral distribution in MCF-7 cells and a cytoplasmic pattern in MDA-MB-231 cells; Rab27A is localized at the cell periphery in MDA-MB-231 cells and in the cytoplasm in MCF-7 cells. Both we and Wang et al obtained the cell lines directly from ATCC [3,15]. Differences in Rab27 expression and localization could be attributed to failure of Rab27B-specific primers in the semi-quantitative PCR assay or the lack of specificity of the Rab27A antibody used by Wang and coworkers.…”
Section: Rab27b-mediated Vesicle Transport Regulates Breast Cancer Cementioning
confidence: 91%
“…Rab27A mRNA and protein levels increased with the in vitro invasive potential of the breast cancer cells studied [15]. Using semi-quantitative real-time RT-PCR and primers and PCR conditions that were not specified, Wang et al found no Rab27B mRNA expression in non-invasive, ER-positive MCF-7 cells, and in invasive ER-negative MDA-MB-231 cells [15]. In contrast, we observed both Rab27A and Rab27B expression in these cells, employing quantitative real-time PCR and Western blotting (Fig.…”
Section: Rab27b-mediated Vesicle Transport Regulates Breast Cancer Cementioning
confidence: 92%
See 1 more Smart Citation
“…Rab27A is also linked with human genetic diseases (Seabra et al, 2002). Rab27A is associated with invasive and metastatic breast cancer, which is facilitated by down-regulation of p16 and up-regulation of cyclinD1 (Wang et al, 2008). Concomitant overexpression of p16 and p73 has oncogenic potential and affects the development and growth of breast carcinomas (Garcia et al, 2004).…”
Section: The Role Of P16mentioning
confidence: 99%